Effect of laser generated shockwaves 1 on ex‐vivo pigskin. Issue 8 (28th August 2014) - Ramaprasad, Vidyunmala; Navarro, Artemio; Patel, Shahzad; Patel, Vikash; Nowroozi, Bryan N.; Taylor, Zach D.; Yong, William; Gupta, Vijay; Grundfest, Warren S.
<x xml:space="preserve">Abstract</x> Introduction Persistent bacterial infection prolongs hospitalizations, leading to increased healthcare costs. Treatment of these infections costs several billion dollars annually. Biofilm production is one mechanism by which bacteria become resistant. With the help of biofilms, bacteria withstand the host immune response and are much less susceptible to antibiotics. Currently, there is interest in the use of laser‐generated shockwaves (LGS) to delaminate biofilm from infected wound surfaces; however, the safety of such an approach has not yet been established. Of particular concern are the thermal and mechanical effects of the shockwave treatment on the epidermis and the underlying collagen structure of the dermis. The present study is a preliminary investigation of the effect of LGS on freshly harvested ex vivo porcine skin tissue samples. Materials and Methods Tissue samples for investigation were harvested immediately post‐mortem and treated with LGS within 30 minutes. Previous studies have shown that laser fluences between 100 and 500 mJ/pulse are capable of delaminating biofilms off a variety of surfaces, thus our preliminary investigation focused on this range of laser energy. For each sample, LGS were produced via laser irradiation of a thin layer (0.5 µm) of titanium sandwiched between a 50 and 100 µm thick layer of water glass and a 0.1 mm thick sheet of Mylar. The rapid thermal expansion of the irradiated titanium film generates a transient compressive wave that is coupled through a liquid layer to the surface of the ex vivo pigskin sample. Shocked samples were immediately fixed in formalin and prepared for histological analysis. A blinded pathologist evaluated and scored each section on the basis of its overall appearance (O) and presence of linear/slit‐like spaces roughly parallel to the surface of the skin (S). The scores were given on a scale of 0–3. Results The present investigation revealed no visible difference between the tissue sections of the control sample and those that were subjected to laser‐generated shockwaves. There was no relationship between the scores received by the samples and the energy with which they were shocked. Conclusion Preliminary investigation into the safety of the LGS treatment for biofilm delamination appears promising. Additional investigation will continue on ex vivo porcine samples, followed by an in vivo animal trial to better understand the physiological response to LGS treatment. Lasers Surg. Med. 46:620–627, 2014. © 2014 Wiley Periodicals, Inc.